The Effect Of Current Ratio (CR) and Debt to Equity Ratio (DER) On Return On Asset (ROA) (Study at PT. Suryamas Dutamakmus, Tbk) - Salmiyah Thaha; Mayang Sari (Movere Journal, 2023)
This study aims to determine the development of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA) and to determine the effect of CR and DER on ROA either partially or simultaneously. The research method used is a quantitative method, namely research that analyzes and describes in detail the condition of the company using data from financial reports. The research object is PT. Suryamas Dutamakmur, Tbk. The financial report data used is 2012 – 2022. The results of the Current Ratio (CR) study have an effect and are not significant on Return On Assets at PT. Suryamas Dutamakmur, Tbk. This is evidenced by the results of the tcount value of 0.903 and ttable of 2.776 with a significance value (sig) of 0.335 where the value of 0.335 > 0.05. The results of the Debt to Equity (DER) study have an effect and are not significant on Return On Assets at PT. Suryamas Dutamakmur, Tbk. this can be proven from the results of the tcount value of 0.280 and ttable of 2.776 with a significant value (sig) of 0.950 where the value of 0.950 > 0.05. The results of the study simultaneously Current Ratio (CR) and Debt to Equity Ratio (DER) have an effect and are not significant on Return On Assets (ROA) at PT Suryamas Dutamakmur, Tbk. This can be proven from the results of obtaining an Fcount value of 0.632 and Ftable of 5.79 with a significant value of 0.632 where the value of 0.997 > 0.05.